Cytoarchitectonic Areas of the Gyrus ambiens in the Human Brain - Insausti, Ricardo; Córcoles-Parada, Marta; Ubero, Mar Maria; Rodado, Adriana; Insausti, Ana Maria; Muñoz-López, Mónica (Frontiers in Neuroanatomy, 2019)
The Gyrus ambiens is a gross anatomical prominence in the medial temporal lobe, associated closely with Brodmann area 34. It is formed largely by the medial intermediate subfield of the entorhinal cortex (Brodmann area 28). Although the medial temporal lobe has been widely studied due to its well-known role on memory and spatial information, the anatomical relationship between Gyrus ambiens, Brodmann area 34, and medial intermediate entorhinal cortex subfield has not been completely defined, in particular whether Brodmann area 34 is part of the entorhinal cortex or a different type of cortex. In order to clarify this issue, we carried out a detailed analysis of 37 human medial temporal lobes, determining the exact location of medial intermediate entorhinal cortex subfield and its extent within the Gyrus ambiens, its cortical thickness, and the histological-MRI correspondence of the Gyrus ambiens with the medial intermediate entorhinal cortex subfield in 10 ex vivo MRI. Our results show that the Gyrus ambiens is limited between two small sulci in the medial aspect of the medial temporal lobe, which correspond almost perfectly to the extent of the medial intermediate entorhinal cortex subfield, although the rostral and caudal extensions of the Gyrus ambiens may extend to the olfactory (rostrally) and intermediate (caudally) entorhinal subfields. Moreover, the cortical thickness averaged 2.5mm (1.3mm for layers I-III and 1mm for layers V-VI). Moreover, distance among different landmarks visible in the MRI scans which are relevant to the identification of the Gyrus ambiens in MRI are provided. These results suggest that Brodmann area 34 is a part of the entorhinal cortex that fits best with the medial intermediate subfield. The histological data, together with the ex vivo MRI identification and thickness of these structures may be of use when assessing changes in MRI scans in clinical settings, such as Alzheimer disease.